Regional Differences of Guillain-Barré Syndrome in China: From South to North - Yao, Jiajia; Liu, Yin; Liu, Shuping; Lu, Zuneng (Frontiers in Aging Neuroscience, 2022)
Background The epidemiological features of Guillain-Barré syndrome (GBS) were different in different areas; a comparison of the disease was needed to identify the variation and prognosis. We compare the epidemiological features of GBS in different areas in China. Method A total of 1,191 patients were included. Information was collected in patients diagnosed with GBS and its variants in middle and south China, and then retrospectively reviewed. The patients were divided into four different regions: East China (n = 441), Center China (n = 566), South China (n = 77), and Southwest China (n = 107). These subregions are mainly divided by climate and geographical location. These data were compared with data from a study in East China (Shandong, n = 150) and Northeast China (Changchun, n = 750). Results Patients from the south and southwest China were younger than other regions (P = 0.000). A summer peak and an autumn peak were found in northern China, but more patients in winter and spring days in other areas (P = 0.000). Upper respiratory tract infection (URTI) was the preceding event of GBS patients in all regions but rarer in central China (P = 0.001). The proportion of axonal subtype was higher in central and southwest China than in other regions (P = 0.001). Patients in southwest China were more served at nadir and have the longest hospital stay (P = 0.003 and P = 0.000). Conclusion The difference between seasonal variation and preceding events was found in different regions in China; clinical features differ among regions in China.